Optimization of Increasing Productivity Making Onion Crackers with Ergonomic Discipline Approach - Mujiono; Sujianto (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
The results of observations made by the research team at MSME (Micro, Small and medium Enterprises) of onion crackers in the cracker cutting section found that for cutting they still use manual tools, namely knives by bending the cutting method so they get tired easily, take a long time and the results are not homogeneous so the results are less optimal. Optimal is meant to be efficient and effective at the available resources, in order to get as much profit as possible by keeping costs as low as possible, by designing an ergonomic cracker cutter. The purpose of designing ergonomic tools in question is the design of tools that produce a work system using anthropometric measurements, focused on designing ergonomic cracker cutting tools that can be used by operators with more effective, efficient, safe, comfortable results and can increase productivity. In this case, the solution that can be done is to design a tool for cutting crackers using anthropometric measurements with the results: tool height 102.5 cm, tool length 52.9 cm, tool width 51.8 cm, and machine handle diameter length of 2.5 cm. From the calculation results, the results obtained if using the old tool the standard output is 3 kg/hour, whereas if using the new tool the standard output is 9.18 kg/hour, so that the productivity is 206%.